Flipped Classroom: Its Planning and Implementation During the Pandemic and Post-Pandemic In Islamic University - Rohmawati, Silfiyah (UIN Syekh Wasil Kediri, Indonesia, 2021)
The COVID-19 pandemic affected not only profoundly negative impact, but also inspired an innovative learning model, especially Arabic learning at the Faculty of Dakwah, UIN Khas Jember. Lecturer and students used technology as a flipped classroom learning medium during the pandemic and post-pandemic. This study is carried out to describe 1) The planning for flipped classroom in Arabic learning during the pandemic and post-pandemic, 2) The implementation of flipped classroom in Arabic learning during the pandemic and post-pandemic. This study is qualitative research with a case study design approach. While, the presentation is focus on the explicit data collection activities of interview, observation, and documentation, as well as triangulation of sources and techniques for data validity. The data is analyzed with the interactive analysis of Miles and Huberman. The results conclude that 1) The lecturer has planned the objectives, materials, media, activities, and assessments before implementing the flipped classroom in Arabic learning, 2) The flipped classroom model that applied in Arabic learning at the Faculty of Dakwah is a traditional and mastery models. And during the pandemic, synchronous and asynchronous classes had been implemented by online, while in the post-pandemic period, asynchronous classes and face-to-face classes had been implemented on campus.